ENTREPRENEURSHIP – A LADDER FOR THE DEVELOPMENT - Zobedha, B. (International Journal of Psychosocial Rehabilitation, 2020)
Entrepreneurship is a term which is an economic activity and which functions in sociological and cultural environment. It could be considered as a person’s free choice activity or a social group’s occupation or profession. The basic concept of entrepreneurship entails an effective and deliberate inner urge to take risk in terms of uncertainties and an intuition. In other words, an entrepreneur shows erudition to jump into untested waters and face the consequences, with a strong self-conviction that he will successfully encounter the sharks and befriend the dolphins.